2020
DOI: 10.1051/e3sconf/202016901012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the genotoxicity of water and soil in the places of storage of reserves of old pesticides by Allium-test

Abstract: Pesticides and persistent organic pollutants (POPs) are a serious environmental problem for almost all countries of the world. The toxic and mutagenic activity of samples of natural water and water extracts of soils collected near the storage sites of old and prohibited pesticides located in the villages of Kyzylkairat, Amangeldy, Beskainar, Belbulak, Enbekshi. Territories of comparison Basshi village (Altyn Emel National Park) and near farmland, where pesticides were used in the past (Taukaraturk village, Alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a similar study, diverse forms of chromosomal aberrations viz., micronucleus, C-mitosis and anaphase bridges etc. in roots of A. cepa developed in soil extract obtained from the pesticide contaminated sites ( Cherednichenko et al., 2020 ). Bianchi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, diverse forms of chromosomal aberrations viz., micronucleus, C-mitosis and anaphase bridges etc. in roots of A. cepa developed in soil extract obtained from the pesticide contaminated sites ( Cherednichenko et al., 2020 ). Bianchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, diverse forms of chromosomal aberrations viz., micronucleus, C-mitosis and anaphase bridges etc. in roots of A. cepa developed in soil extract obtained from the pesticide contaminated sites (Cherednichenko et al, 2020). Bianchi et al observed that the combination of the insecticide imidacloprid with the herbicide sulfentrazone poses a danger to organisms due to the possibility for chromosomal damage and a delay in cell cycle development (Bianchi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%